2020
DOI: 10.1021/acsapm.0c01025
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Rapid Naked-Eye Colorimetric Sensing and Fluorescent Studies of Cu2+ Ions Derived from Spherical Nanocellulose

Abstract: Nanocellulose has emerged as the most promising sustainable nanomaterial to develop cost-effective smart materials for various applications with consequential positive environmental impact. In the present study, we report spherical nanocellulose (SNC) modified with diethylenetriamine (DETA) and/or ethanolamine (EA) (SNC-DETA, SNC-EA, and SNC-DETA-EA) as Cu2+ ion sensors. Structure dependence of the sensing properties is the highlight of this work, as SNC-DETA-EA and SNC-DETA showed colorimetric naked-eye and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Other colorimetric sensors detect Cu 2+ using nanocellulose or Hg 2+ using GNPs, and DNAzymes have not yet been used to detect SARS‐CoV‐2 but were similarly not evaluated using environmental samples. [ 22,23 ] These colorimetric tests have been successful when detecting pure or spiked samples, but the challenge arises when clinical samples are used.…”
Section: Resultsmentioning
confidence: 99%
“…Other colorimetric sensors detect Cu 2+ using nanocellulose or Hg 2+ using GNPs, and DNAzymes have not yet been used to detect SARS‐CoV‐2 but were similarly not evaluated using environmental samples. [ 22,23 ] These colorimetric tests have been successful when detecting pure or spiked samples, but the challenge arises when clinical samples are used.…”
Section: Resultsmentioning
confidence: 99%
“…133 It was further reported that spherical NC (SNC) was modified with diethylenetriamine (DETA) and/or ethanolamine (EA) (i.e., SNC−DETA and SNC−DETA−EA) to develop a highly selective and rapid sensor for Cu ions (Cu 2+ ), visible with the naked eyes, via colorimetric sensing and fluorescence. 134 The study demonstrated that the SNC−DETA−EA exhibited a distinctive structure−property relationship through these well-defined selective colorimetric and fluorometric sensing characteristics toward Cu 2+ . Therefore, it was possible to observe the fluorescent quenching behavior upon the addition of Cu 2+ ions even at low concentrations with the naked eye (Figure 9).…”
Section: Nanocellulosics: Efficient and Benign Water Remediation And ...mentioning
confidence: 91%
“…Therefore, it was possible to observe the fluorescent quenching behavior upon the addition of Cu 2+ ions even at low concentrations with the naked eye (Figure ). Moreover, this biocomposite sensor demonstrated good tolerance to pH variations, in addition to the added advantages of recyclability and reversibility …”
Section: Nanocellulosics: Efficient and Benign Water Remediation And ...mentioning
confidence: 99%
See 2 more Smart Citations